Synthesis, Structural Characterization and Antibacterial Activity of 2,6-diacetylpyridine bis(benzenesulfonohydrazide) Schiff Bases and Their Copper(II) Complexes - Yusnita, J.; Puvaneswary, S.; Ali, H.M.; Robinson, W.T.; Thong, Kwai Lin (Elsevier, 2009)
2,6-Diacetylpyridine bis(benzenesulfonohydrazide) Schiff bases (L(1), L(2) and L(3)) and their Cu(II) complexes of the general formula CuL center dot H(2)O were synthesized and characterized by various spectroscopic techniques. The crystal structure of CuL(3)center dot(py)center dot py was investigated by single crystal X-ray structure analysis. The Cu(II) cation has near square pyramidal, penta-coordinate geometry. The binegatively charged tetradentate Schiff base is asymmetrically coordinated to the Cu(II) ion via the pyridine N atom, the azomethine N atom, the sulfonyl O atom and the deprotonated hydrazine N atom. There is a pyridine molecule apically coordinated to the Cu(II) ion. All the Schiff bases and their copper(II) complexes were screened by the disc diffusion method against multi-drug resistant (MDR) gram-negative and gram-positive bacteria. The minimum inhibitory concentration (MIC) values were also determined. These results show that the antibacterial activity of the Schiff bases against Methicillin-resistant Staphylococcus aureus (MRSA) is enhanced when they are chelated with the copper(II) ion. Crown Copyright (C) 2009 Published by Elsevier Ltd. All rights reserved.